How to improve accountability of fixed assets of local government? - Sri Rahayu; Yudi Yudi; Rahayu Rahayu (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
Accountability of assets is an unfinished problem in almost all local governments in Indonesia. It is proved by the high number of audit findings from the State Audit Agency regarding asset management issues. The aim of this study is to analyze the implementation of the accountability of fixed assets of local government. The method used is qualitative method. Questionnaires and interviews were done for data collection. The respondents of the research are government officials and apparatus who are actively involved in managing regional assets. The result shows that the implementation of the legal and process accountability for fixed asset management in Jambi City is categorized as good.